Pengaruh edukasi dengan video animasi getar “gempa tanggap dan responsif” terhadap pengetahuan kesiapsiagaan gempa bumi pada siswa - Nurfalahi, Salma Cinta; Sutrisno; Putra, Fajar Alam (JOURNAL of Public Health Concerns, 2025)
Background: Indonesia is a country with a high risk of natural disasters, particularly earthquakes and volcanic eruptions, due to its location at the confluence of three active tectonic plates: the Indo-Australian, Eurasian, and Pacific. Earthquakes are among the most destructive disasters in the world. Lack of public knowledge about disaster preparedness, including in schools, is a factor that increases disaster risk. One way to increase students' knowledge about disaster preparedness is through engaging learning media such as animated videos. Purpose: To increase students' knowledge of earthquake preparedness through educational media using animated videos. Method: This activity was conducted on April 17, 2025, at Gentungan 1 State Elementary School (SDN), Mojogedang, Karanganyar Regency. A quantitative approach was used with a pre-experimental research method. The population in this study were 105 students in grades 3, 4, 5, and 6 of SDN 1 Gentungan, Karanganyar. The sample size was 52 respondents. The variable of knowledge of earthquake disaster preparedness. The intervention activity is education on knowledge of earthquake preparedness using animated video media. Results: The average age of respondents was 10.67 years with a standard deviation of 1.08 years, with the majority of respondents aged 9-12 years (15 (28.9%) being under 12 years old. The majority were female (32 (61.5%), and the majority were sixth-grade students (16 (30.7%). The pre-test knowledge level was in the very good category (4 (7.7%), and the post-test knowledge level was in the very good category (22 (42.3%). Conclusion: Educational activities on earthquake disaster preparedness through visual and audio-based learning significantly improved student understanding. Animated video media not only provided information but also presented it in an engaging, simple, and easy-to-understand manner. Keywords: Animated video; Disaster preparedness; Elementary school students; Knowledge Pendahuluan: Indonesia adalah negara dengan risiko bencana alam yang tingggi, terutama gempa bumi dan letusan gunung berapi, keran lokasinya dipertemuan tiga lempeng tektonik aktif yaitu indo-australia, Eurasia. Dan pasifik, Gempa bumi termasuk bencana paling merusak di dunia. Kurangnya pengetahuan kesiapsiagaan masyarakat, termasuk di lingkungan sekolah, dalam menghadapi bencana alam menjadi salah satu faktor yang memperbesar risiko bencana. Salah satu cara untuk meningkatkan pengetahuan siswa tentang kesiapsiagaan bencana adalah melalui media pembelajaran menarik seperti video animasi. Tujuan: Untuk meningkatkan pengetahuan siswa dalam kesiapsiagaaan terhadap gempa bumi berupa edukasi dengan media video animasi. Metode: Kegiatan ini dilaksanakan pada tanggal 17 April 2025 di Sekolah Dasar Negeri (SDN) Gentungan 1 Mojogedang Kabupaten Karanganyar. Menggunakan pendekatan kuantitatif dengan jenis penelitian pre-ekspremental. Populasi pada penelitian ini adalah siswa kelas 3, 4, 5, dan 6 SDN 1 Gentungan Karanganyar yang berjumlah sebanyak 105 siswa. Sampel yang digunakan 52 responden. Variabel pengetahuan kesiapsiagaan bencana gempa bumi.Kegiatan intervensinya adalah edukasi pengetahuan kesiapsiagaan gempa bumi dengan media video animasi. Hasil: Mendapatkan rata-rata usia responden adalah 10.67 tahun dengan standar deviasi 1.08 tahun dalam rentang usia 9-12 tahun dan sebagian besar usia responden adalah 12 tahun sebanyak 15 (28.9%), Mayoritas jenis kelamin perempuan sebanyak 32 (61.5% dan sebagian besar siswa kelas 6 sebanyak 16 (30.7%). Sedangkan tingkat pengetahuan (pre-test) kategori sangat baik sebanyak 4 (7.7%) dan tingkat pengetahuan (post-test) kategori sangat baik sebanyak 22 (42.3%) Simpulan: Kegiatan edukasi pengetahuan kesiapsiagaan bencana gempa bumi melalui pembelajaraan berbasis visual dan audio mampu meningkatkan pemahaman peserta didik secara signifikan, media video animasi tidak hanya memberikan informasi, tetapi juga menyajikannya dengan cara yang menarik, sederhana dan mudah untuk diterima.